PENDIDIKAN BERTANGGUNG JAWAB MEWUJUDKAN MASYARAKAT INDONESIA BARU - Haryanto Haryanto (LPMPP Universitas Negeri Yogyakarta, 2001)
Tile discourse ()n tile civil society as tIle new Indonesian society Wllicll las beenreverberating in society lately is still in tile pllase ofslogans being discussed and debated upon.ll1e concept GIld reali:=ation ofsuch a type oj